1992
DOI: 10.1111/j.1365-2044.1992.tb02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper oesophageal sphincter pressure and the effect of cricoid pressure

Abstract: SummaryUpper oesophageal sphincter pressure has been measured in 24 patients with a sleeve device. The median sphincter pressure when awake was 38 mmHg. and when anaesthetised and paralysed was 6 mmHg. Afier tracheal intubation, cricoid pressure was applied at measured values between 5 and 50 N using a hand-held cricoid yoke while the sphincter pressure was recorded in two head and neck positions: with and without a standard intubating pillow with neck support. A cricoid ,force of 40 N increased sphincter pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
4

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 28 publications
(14 reference statements)
2
69
0
4
Order By: Relevance
“…The upper esophageal sphincter may not be important in preventing gastro-oesophageal insufflation. 21 We can offer two possible explanations for our findings. First, the face mask technique requires the anaesthetist to seal the mask against the skin of the face.…”
Section: Resultsmentioning
confidence: 85%
“…The upper esophageal sphincter may not be important in preventing gastro-oesophageal insufflation. 21 We can offer two possible explanations for our findings. First, the face mask technique requires the anaesthetist to seal the mask against the skin of the face.…”
Section: Resultsmentioning
confidence: 85%
“…We previously reported that in anaesthetised and paralysed patients a cricoid force of 40 Newtons increased UOSP to above the median of the awake values in all patients [5]. This level of cricoid pressure is uncomfortable and vomiting has followed its application resulting in death from aspiration pneumonitis in one patient [33], and rupture of the oesophagus in another [34].…”
Section: Discussionmentioning
confidence: 99%
“…The upper oesophageal sphincter can also prevent the regurgitation of oesophageal contents during light general anaesthesia in the absence of neuromuscular blockade [2, 31. Suxamethonium usually causes an abrupt fall in upper oesophageal sphincter pressure (UOSP) with the onset of fasciculations [4]. In those patients at risk of gastro-oesophageal reflux, cricoid pressure counteracts this reduction in UOSP [5]. However, there is controversy about when cricoid pressure should be applied: before loss of consciousness [6, 71, or only after loss of consciousness [8,9] in case vomiting is provoked by its application.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nor is cricoid pressure itself entirely straightforward, even trained staff do not consistently apply it correctly [2,3]. Cricoid pressure may also make ventilation harder, paradoxically increasing the likelihood of gastric insufflation.…”
Section: Swindon Wiltshire Sn1 4jumentioning
confidence: 99%